On the Total Overtime Service in Some Loss Queueing Systems - AGRAFIOTIS, G. K. (Institutional Knowledge at Singapore Management University, 1997)
For a GI/G/1 loss queueing system, we find expressions concerning the total overtime service rendered, the total revenue and the time to the arrival of the first customer whose service time exceeds a critical service time. We also discuss the total overtime service rendered by any particular server in a GI/G/K loss system.